HUBUNGAN KOMUNIKASI TERAPEUTIK DENGAN INTENSITAS NYERI PADA PERSALINAN KALA I DI BPM â€œBâ€ BUKITTINGGI TAHUN 2015 - Rahmi Kurnia Gustin; Ella Rosantri (Jurnal Kesehatan - STIKes Prima Nusantara, 2017)
Elderly health service coverage in the health centers Kumanis is the lowest in the Sijunjung 16.7% as much and is still far from close to the target of 70%. The research aims to know the posyandu program implementation elderly health centers Kumanis in the year 2016.The method of research used the qualitative method with evaluative study design. Research conducted in August 2016 in health centers Kumanis, sampling used are purposive sampling. Data collection is done with the interview in depth against the head of the health centers, program manager, posyandu cadre of elderly and elderly, elderly posyandu implementation of the observations and the examination of documents.The results of this study of the component input, not regulation of health service Sijunjung to support program implementation elderly posyandu. Implemented personnel not followed training, there has been no active officers and cadres are still lacking. Infrastructure elderly posyandu no place special. On the components of the process, in general the activities of the elderly at posyandu clinics Kumanis not implemented to its full potential because of the constraints of the program managers or the liveliness of health workers that is not consistent with the work plan so that there are no activities were carried out at the time of posyandu, activities carried out more to physical examination, monitoring and evaluation of optimal running and yet still a lack of awareness and participation of elderly to visit elderly posyandu. On the component output, program execution implemented yet elderly posyandu well and hasn't been able to increase the scope of elderly health services each year. The conclusions of the above study is still the presence of obstacles in the implementation of elderly posyandu health centers in Kumanis on the component inputs and the process of implementation of the activities of the elderly posyandu. Need for support from the management of clinics in order to improve the quality and quantity of the implemented power elderly posyandu.